Untold Stories of the ER : Providing Care During the COVID-19 Pandemic as Narrated by Emergency Room Nurses in Toronto, Ontario, Canada - Marsh, Andrea (Université d'Ottawa / University of Ottawa, 2022)
As the COVID-19 pandemic has taken hold of Toronto, Ontario, Canada, and the world, it has highlighted many challenges healthcare workers face. Those nurses working in the emergency room (ER), settings that are under normal circumstances unpredictable and acute, have been particularly affected. This research aimed to explore the stories ER nurses tell to describe their experiences of working during the COVID-19 pandemic in Toronto, Canada. Narrative methodology was used to understand the thoughts, feelings, and problems facing ER nurses. The research study includes the stories of three Toronto-based ER nurses who share their experiences of working during the COVID-19 pandemic. Participants were interviewed twice, and data was analysed using the three-dimensional narrative inquiry space of time, sociality, and place. Plotlines of 'before they were heroes', 'hero', 'fall from grace', 'villain' and 'to be continued', organized each story. Resounding narrative threads emerged across the three narrative accounts and are presented as understandings. Threads that resonated across the stories include mistrust in leadership, fear and isolation, expectations and duty to care, nursing shortages, personal safety and PPE, workload and stress, moral and psychological distress, and lost voice. The findings of this inquiry offer a new context for understanding the thoughts, feelings, and problems facing ER nurses working in Toronto during the COVID-19 pandemic in a way that preserves, values, and respects the voices and stories of the nurses themselves, thus allowing for emotional healing while offering insight for nursing education, practice, and research.
Keywords: COVID-19; nursing; ER; narrative